Prescription Drug Diversion: Predictors of Illicit Acquisition and Redistribution in Three U.S. Metropolitan Areas - Aikins, Ross (AIMS Public Health, 2015)
Objective: Prescription drug diversion, the transfer of prescription drugs from lawful to unlawful channels for distribution or use, is a problem in the United States. Despite the pervasiveness of diversion, there are gaps in the literature regarding characteristics of individuals who participate in the illicit trade of prescription drugs. This study examines a range of predictors (e.g., demographics, prescription insurance coverage, perceived risk associated with prescription drug diversion) of membership in three distinct diverter groups: individuals who illicitly acquire prescription drugs, those who redistribute them, and those who engage in both behaviors. Methods: Data were drawn from a cross-sectional Internet 763 AIMS Public Health Volume 2, Issue 4, 762-783. study (N = 846) of prescription drug use and diversion patterns in New York City, South Florida, and Washington, D.C.. Participants were classified into diversion categories based on their self-reported involvement in the trade of prescription drugs. Group differences in background characteristics of diverter groups were assessed by Chi-Square tests and followed up with multivariate logistic regressions. Results: While individuals in all diversion groups were more likely to be younger and have a licit prescription for any of the assessed drugs in the past year than those who did not divert, individuals who both acquire and redistribute are more likely to live in New York City, not have prescription insurance coverage, and perceive fewer legal risks of prescription drug diversion. Conclusion: Findings suggest that predictive characteristics vary according to diverter group